Placement of Cacoceria and phylogenetic relationships of the xylotine genera of the tribe Milesiini (Diptera, Syrphidae: Eristalinae) based on molecular characters - Ståhls, Gunilla (Zootaxa, 2006)
The phylogenetic relationships of traditional xylotine genera of tribe Milesiini (Diptera, Syrphidae: Eristalinae) were explored using molecular character of a large fragment of the mitochondrial COI and the D2-3 region of the nuclear ribosomal 28S rRNA gene. Of particular interest was the phylogenetic placement of the enigmatic Neotropical genus Cacoceria. The ingroup included 48 taxa, and Cheilosia illustrata (Rhingiini, Eristalinae) was used as outgroup. Multiple specimens of more common taxa were sequenced for surveying levels of intraspecific variation. The combined dataset was analysed using parsimony and optimisation alignment, using the program POY. Cacoceria was resolved within the Chalcosyrphus clade. Earlier hypotheses placed the taxon in the tribe Myoleptini or Chrysogasterini, or in Xylotini without stating a closer relationship to any particular xylotine taxon. The representatives of traditional xylotine taxa were resolved as ((Hadromyia + (Brachypalpoides + Blera + Lejota) + (Xylota sg. Hovaxylota + Xylota sg. Sterphoides) + (Xylota (including Sterphus)) while Neplas and Brachypalpus were resolved in the Myoleptini albeit with very low support.